Depósitos del aptiano inferior con amonitas y rudistas, Punta Espada, Alta Guajira (Uribia - Colombia): litoestratigrafía y apreciaciones regionales = Lower Aptian deposits with ammonites and rudists, Punta Espada, Alta Guajira (Uribia – Colombia) : lithostratigraphy and regional commentaries - Patarroyo, Pedro; Götz, Stefan (Boletín de geología, 2020)
In the Piedra del Destino valley (Punta Espada, Uribia - La Guajira, Colombia) there are biomicrites, biosparites and calcareous shales that contain Dufrenoyia sp., D. cf. hansbuergli, Cheloniceras sp. Pseudohaploceras cf. liptoviense and Amphitriscoelus waringi with a lower Aptian range. The bibliography relate that those deposits are part of the Cogollo Formation, but taken into account the lithostratigraphical analysis, fossil fauna, tectonic and body rock continuity, it is not recommendable to apply the lithostratigraphical nomenclature from western Venezuela to the Alta Guajira region where are evolved the Punta Espada Cretaceous deposits. The collected fossils show both influence of the Tethys domain and as regional provincialism.
Gesehen am 05.12.2025